Demographics and Clinical and Endoscopic Characteristics of Patients with Helicobacter pylori Infection and Gastroesophageal Reflux Disease: A Case-Control Study. (6th May 2019) - Mari, Amir; Mahroum, Naim; Bragazzi, Nicola Luigi; Shalaata, Mahran; Khoury, Tawfik; Watad, Abdulla; Mahamid, Mahmud
Abstract : Background . The correlation between Helicobacter pylori ( H. pylori ) and gastroesophageal reflux disease (GERD) is complex. Some studies showed a protective role of H. pylori infection against GERD. This study was aimed at assessing the role of H. pylori infection in GERD utilizing a large cohort of patients diagnosed with GERD. Methods and Materials . All patients who underwent gastroscopy for an indication of GERD during the study period between 2015 and 2017 at the EMMS Nazareth Hospital were considered eligible for the study and therefore were included. H. pylori infection was determined by the rapid urease test or histology. Severity of esophagitis was assessed using the Los Angeles classification. Univariate analysis was performed to figure out differences between patients according to H. pylori infection status. Multivariate regression analysis was conducted to illustrate the predictors of positivity for H. pylori infection. Results . 2, 508 GERD patients were included with a median age of49.42 ± 17.96 years. H. pylori infection was detected in 299 (11.9%) patients. GERD patients with H. pylori infection were found to be younger (48.83 ± 17.42 years versus44.57 ± 17.69 years, p < 0.001 ), have the tendency to smoke more (1406 (63.6%) versus 266 (89.0%), p < 0.001 ), and use more proton pump inhibitors or PPIs (1314 (59.5%) versus 242 (80.9%), p < 0.001 ). In multivariate regression analysis, age (OR 0.987, p < 0.001 ), smoking status (OR 0.190, p < 0.001 ), use of ASA/NSAIDs (OR 1.652, p = 0.004 ), and use of statins (OR 0.499 (95%CI 0.295-0.846), p = 0.010 ) were found significant among H. pylori -positive individuals. H. pylori -positive subjects have less severe esophagitis and more hiatus hernia. Conclusion . Patients with GERD and H. pylori infection were significantly younger, tended to smoke more, and used more PPIs and had significantly lower grades of esophagitis compared to noninfected ones.